Introducing Inclusive Sports Programs in the Educational System of Schools - Nikšić, Elvira; Ajla Bukva, Ajla Bukva (Jurnal Moderasi Olahraga, 2024)
This research aims to examine and determine the attitudes, i.e. the interest of teachers, physical and health education teachers, and parents for the introduction of inclusive sports programs in the educational system of schools that would be integrated and available to all students regardless of the abilities, opportunities, individuality of each child as and to difficulty. The research was conducted on a sample of N=426 respondents, of which there were N=370 parents, N=49 teachers, and N=7 physical and health education teachers. For the implementation of this research, a survey method was used through the application of questionnaires/attitude scales for teachers, physical and health education teachers, and parents. We processed the research results using descriptive statistics, frequencies, and percentages and presented them tabularly and graphically. The total number of students in the four elementary schools where the research was conducted is N=1082 students, of which there were N=16 students with developmental disabilities. Of these, 14 students work according to an individual plan and program (IPP), and 13 students have a teaching assistant. Out of a total of N=1082 students, 292 students with typical development attend one of the school sections, and 2 students with developmental difficulties. Parents, teachers, and teachers are in favor of introducing inclusive sports programs into the educational system of schools that would be integrated and accessible to all students, regardless of the abilities, opportunities, and individuality of each child, as well as the difficulty.